A method for preparing ceramic material of bamboo charcoal pot

By using raw materials such as bamboo charcoal powder and using wet ball milling, hot pressing and firing molding, bamboo charcoal pot ceramic materials with improved impact resistance, heat conductivity and wear resistance are prepared, which solves the problem of poor coordination of existing bamboo charcoal pots and significantly improves the product's cold and cold resistance and scrubbing stability.

CN119241243BActive Publication Date: 2025-03-07FUJIAN HUAXIA VAJRA TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411764272.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-07
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

The impact, thermal conductivity and wear resistance of existing bamboo charcoal pots are difficult to coordinately improve, and their cold and cold resistance and scrubbing stability are poor, which limits the efficiency of the product.

Method used

Bamboo charcoal pot ceramic materials with improved impact resistance, thermal conductivity and wear resistance are prepared by wet ball milling, hot pressing molding and firing molding.

Benefits of technology

It significantly coordinates and improves the product's impact, thermal conductivity and wear resistance, and improves the product's cold and cold resistance and scrubbing stability, improving its use efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the field of ceramic technology, and specifically discloses a method for preparing a ceramic material for a bamboo charcoal pot, comprising the following steps: weighing raw materials according to weight, 25 to 30 parts of bamboo charcoal powder, 20 to 25 parts of quartz powder, 10 to 15 parts of silicon carbide, 10 to 14 parts of a balancing agent based on whisker compounding, 8 to 12 parts of albite, 7 to 11 parts of a filler modified by doping magnesium oxide, and 5 to 10 parts of clay. The ceramic material for a bamboo charcoal pot of the invention adopts bamboo charcoal powder, quartz powder, silicon carbide, albite, and clay raw materials, and by adding a balancing agent based on whisker compounding and a filler modified by doping magnesium oxide, the impact resistance, thermal conductivity and wear resistance of the product are improved in a coordinated manner, and the cold and heat resistance and scrubbing stability of the product are remarkable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramics, and in particular to a method for preparing a ceramic material for a bamboo charcoal pot. Background Art

[0002] Bamboo has high strength and good toughness, and the bamboo charcoal produced from the raw materials is green and environmentally friendly. The bamboo charcoal pot is a pot made by hand-polishing the bamboo after roasting it into powder. The bamboo charcoal pot does not contain heavy metals, is green, healthy and safe, and can be used on open flame induction cookers.

[0003] The existing bamboo charcoal pot is made of bamboo charcoal as raw material. The impact resistance, thermal conductivity and wear resistance of the product are difficult to coordinate and improve. In addition, the product has poor resistance to cold and heat and scrubbing stability, which limits the use efficiency of the product. Based on this, the present invention further improves it. Summary of the invention

[0004] In view of the defects of the prior art, the purpose of the present invention is to provide a method for preparing a ceramic material for a bamboo charcoal pot to solve the problems raised in the above background technology.

[0005] The present invention solves the technical problem by adopting the following technical solution:

[0006] The present invention provides a method for preparing a ceramic material for a bamboo charcoal pot, comprising the following steps:

[0007] Step 1: weigh the raw materials according to weight: 25-30 parts of bamboo charcoal powder, 20-25 parts of quartz powder, 10-15 parts of silicon carbide, 10-14 parts of whisker-based counterbalancer, 8-12 parts of albite, 7-11 parts of magnesium oxide-doped filler, and 5-10 parts of clay;

[0008] Step 2: wet-milling the raw material in step 1 at a ball milling speed of 1000-1500 r / min for 2 h to obtain a ball milled material;

[0009] Step 3: hot-press the ball mill material into a mold, the hot-pressing pressure is 10-15 MPa, the pressure time is 1-2 hours, the hot-pressing temperature is 60-65°C, and the hot-pressing is completed to obtain a ball mill body;

[0010] Step 4: The ball mill is fired and formed, and after the firing is completed, the bamboo charcoal pot ceramic material is obtained.

[0011] Preferably, the sintering and molding process is first sintered at a temperature of 550-570° C. for 1 hour, then heated to 1100-1150° C. at a rate of 2° C. / min and sintered for 2 hours.

[0012] Preferably, the preparation method of the whisker-based counterbalancing agent is:

[0013] S01: stirring and mixing the aluminum borate whiskers in a sufficient amount of a 5% by mass hydrochloric acid solution, and then washing, filtering and drying to obtain dry aluminum borate whiskers;

[0014] S02: Add 3 to 5 parts of nano titanium dioxide and 1 to 3 parts of cerium oxide to 4 to 7 parts of sodium lignin sulfonate solution by weight, and then add 1 to 2 parts of stearic acid, mix well, and obtain a modified solution;

[0015] The dried aluminum borate whiskers and the modified liquid are stirred and modified in a weight ratio of 2:5, and after the stirring is completed, the mixture is filtered and dried to obtain the modified aluminum borate whiskers;

[0016] S03: The modified aluminum borate whiskers and the balancing liquid are mixed and ball-milled in a weight ratio of 5:3. After the ball-milling is completed, the mixture is washed with water, filtered and dried to obtain a whisker-based polyvalent balancing agent.

[0017] Preferably, the mass fraction of the sodium lignin sulfonate solution is 2-5%; the stirring speed of the stirring modification treatment is 550-750 r / min, and the stirring time is 20-30 min.

[0018] Preferably, the mixing and ball milling treatment is performed at a ball milling speed of 1000 to 1200 r / min, and the ball milling is performed for 2 hours.

[0019] Preferably, the balance solution comprises the following raw materials in parts by weight:

[0020] 4 to 6 parts of nano-montmorillonite, 3 to 4 parts of dopamine hydrochloride solution, 1 to 3 parts of chitosan solution, 2 to 3 parts of silicon carbide and 1 to 2 parts of lanthanum oxide.

[0021] Preferably, the mass fraction of the dopamine hydrochloride solution is 2-5%; the mass fraction of the chitosan solution is 3-6%.

[0022] Preferably, the preparation method of the magnesium oxide-doped filler is:

[0023] S11: stirring the sepiolite fiber in a sufficient amount of a 5% by mass potassium permanganate solution, then washing, filtering, and drying to obtain dry sepiolite fiber;

[0024] By weight, 4-7 parts of dry sepiolite fiber, 1-3 parts of silane coupling agent KH550, 2-6 parts of sodium silicate solution and 1-3 parts of heavy calcium carbonate are mixed and stirred to obtain a fiber liquid;

[0025] S12: preheating aluminum nitride at 60-65° C. for 15-20 minutes to obtain preheated aluminum nitride; stirring the preheated aluminum nitride and fiber liquid in a weight ratio of 3:(5-7), and completing the stirring to obtain a fiber-adjusted aluminum nitride agent;

[0026] S13: heat treating the nano magnesium oxide at 260-270° C. for 10-15 min, then cooling to 55° C. at a rate of 1-3° C. / min, and keeping the temperature to obtain the heat-insulated nano magnesium oxide;

[0027] The nano-magnesium oxide is immersed in a sufficient amount of lanthanum nitrate solution and fully ultrasonicated, and then filtered and dried to obtain lanthanum-doped nano-magnesium oxide;

[0028] S14: The lanthanum-doped nano-magnesium oxide and the aluminum nitride agent blended with the fiber are mixed and ball-milled in a weight ratio of 5:3 at a ball-milling speed of 1500 r / min for 1 h. After the ball-milling is completed, the mixture is filtered and dried to obtain a magnesium oxide-doped modified filler.

[0029] Preferably, the mass fraction of the sodium silicate solution is 3-5%; the mass fraction of the lanthanum nitrate solution is 4-6%.

[0030] Preferably, the stirring speed of the stirring treatment in S12 is 550-750 r / min, and the stirring time is 35-45 min; the ultrasonic power of the ultrasonic immersion in S13 is 350-400 W, and the ultrasonic time is 20-30 min.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] 1. The ceramic material of the bamboo charcoal pot of the present invention adopts bamboo charcoal powder, quartz powder, silicon carbide, albite and clay raw materials, and by adding a balance agent based on whisker polyphony and a filler modified by doping magnesium oxide, the impact resistance, thermal conductivity and wear resistance of the product are improved through the coordination and coordination between the raw materials, and the cold and heat resistance and scrubbing stability of the product are significantly improved;

[0033] 2. The whisker-based compounding balance agent uses aluminum borate whiskers as a matrix in the preparation, is activated by a hydrochloric acid solution, and then improved by a modifying liquid. Nano titanium dioxide and cerium oxide in the modifying liquid are mixed into a sodium lignin sulfonate solution, and are improved by blending with stearic acid. The nano titanium dioxide in the modifying liquid is improved to treat aluminum borate whiskers. The whisker structure is matched with point-shaped nano titanium dioxide to optimize the coordination and improvement effect of the modified aluminum borate whiskers and the balance liquid. Nano montmorillonite, dopamine hydrochloride solution, chitosan solution, silicon carbide and lanthanum oxide are mixed and formulated in the balance liquid. Silicon carbide is blended with layered nano montmorillonite to enhance the performance stability of the product system. At the same time, dopamine hydrochloride solution, chitosan solution and lanthanum oxide are blended again. The raw materials are coordinated to obtain a whisker-based compounding balance agent that can optimize the performance coordination of the system in the product and improve the performance stability of the system.

[0034] 3. The filler modified by doping magnesium oxide adopts sepiolite fiber treated with potassium permanganate solution to optimize the active efficiency of sepiolite fiber. At the same time, sepiolite fiber has unique physical and chemical properties, high specific surface area and high porosity. After the silane coupling agent KH550, sodium silicate solution and heavy calcium carbonate are blended and matched to obtain fiber liquid, it is used to reinforce and improve the preheated aluminum nitride, so as to utilize the high specific surface area and porosity to have the effect of carrying aluminum nitride and heavy calcium carbonate, thereby better reinforcing the performance of the system and optimizing the performance. Coordination and performance stability, the nano magnesium oxide is heat treated at 260-270°C for 10-15 minutes, and then cooled to 55°C at a rate of 1-3°C / min, and kept warm to improve the activity of the nano magnesium oxide, and then immersed in ultrasound through a lanthanum nitrate solution to better blend the lanthanum-doped nano magnesium oxide into the fiber-blended aluminum nitride agent, so that the prepared doped magnesium oxide-modified filler can better optimize the system performance effect in the system, enhance the product performance stability, and then the product performance is further improved. DETAILED DESCRIPTION

[0035] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] The method for preparing a bamboo charcoal pot ceramic material of the present embodiment comprises the following steps:

[0037] Step 1: weigh the raw materials according to weight: 25-30 parts of bamboo charcoal powder, 20-25 parts of quartz powder, 10-15 parts of silicon carbide, 10-14 parts of whisker-based counterbalancer, 8-12 parts of albite, 7-11 parts of magnesium oxide-doped filler, and 5-10 parts of clay;

[0038] Step 2: wet-milling the raw material in step 1 at a ball milling speed of 1000-1500 r / min for 2 h to obtain a ball milled material;

[0039] Step 3: hot-press the ball mill material into a mold, the hot-pressing pressure is 10-15 MPa, the pressure time is 1-2 hours, the hot-pressing temperature is 60-65°C, and the hot-pressing is completed to obtain a ball mill body;

[0040] Step 4: The ball mill is fired and formed, and after the firing is completed, the bamboo charcoal pot ceramic material is obtained.

[0041] The sintering process of this embodiment first adopts a sintering temperature of 550-570° C. for 1 hour, and then increases the temperature to 1100-1150° C. at a rate of 2° C. / min and sintering for 2 hours.

[0042] The preparation method of the whisker-based balancing agent of this embodiment is as follows:

[0043] S01: stirring and mixing the aluminum borate whiskers in a sufficient amount of a 5% by mass hydrochloric acid solution, and then washing, filtering and drying to obtain dry aluminum borate whiskers;

[0044] S02: Add 3 to 5 parts of nano titanium dioxide and 1 to 3 parts of cerium oxide to 4 to 7 parts of sodium lignin sulfonate solution by weight, and then add 1 to 2 parts of stearic acid, mix well, and obtain a modified solution;

[0045] The dried aluminum borate whiskers and the modified liquid are stirred and modified in a weight ratio of 2:5, and after the stirring is completed, the mixture is filtered and dried to obtain the modified aluminum borate whiskers;

[0046] S03: The modified aluminum borate whiskers and the balancing liquid are mixed and ball-milled in a weight ratio of 5:3. After the ball-milling is completed, the mixture is washed with water, filtered and dried to obtain a whisker-based polyvalent balancing agent.

[0047] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 2-5%; the stirring speed of the stirring modification treatment is 550-750 r / min, and the stirring time is 20-30 min.

[0048] The mixing ball milling process of this embodiment has a ball milling speed of 1000-1200 r / min and the ball milling is performed for 2 hours.

[0049] The Lianheng liquid of this embodiment includes the following raw materials in parts by weight:

[0050] 4 to 6 parts of nano-montmorillonite, 3 to 4 parts of dopamine hydrochloride solution, 1 to 3 parts of chitosan solution, 2 to 3 parts of silicon carbide and 1 to 2 parts of lanthanum oxide.

[0051] The mass fraction of the dopamine hydrochloride solution in this embodiment is 2-5%; the mass fraction of the chitosan solution is 3-6%.

[0052] The preparation method of the magnesium oxide-doped filler modified in this embodiment is as follows:

[0053] S11: stirring the sepiolite fiber in a sufficient amount of a 5% by mass potassium permanganate solution, then washing, filtering, and drying to obtain dry sepiolite fiber;

[0054] By weight, 4-7 parts of dry sepiolite fiber, 1-3 parts of silane coupling agent KH550, 2-6 parts of sodium silicate solution and 1-3 parts of heavy calcium carbonate are mixed and stirred to obtain a fiber liquid;

[0055] S12: preheating aluminum nitride at 60-65° C. for 15-20 minutes to obtain preheated aluminum nitride; stirring the preheated aluminum nitride and fiber liquid in a weight ratio of 3:(5-7), and completing the stirring to obtain a fiber-adjusted aluminum nitride agent;

[0056] S13: heat treating the nano magnesium oxide at 260-270° C. for 10-15 min, then cooling to 55° C. at a rate of 1-3° C. / min, and keeping the temperature to obtain the heat-insulated nano magnesium oxide;

[0057] The nano-magnesium oxide is immersed in a sufficient amount of lanthanum nitrate solution and fully ultrasonicated, and then filtered and dried to obtain lanthanum-doped nano-magnesium oxide;

[0058] S14: The lanthanum-doped nano-magnesium oxide and the aluminum nitride agent blended with the fiber are mixed and ball-milled in a weight ratio of 5:3 at a ball-milling speed of 1500 r / min for 1 h. After the ball-milling is completed, the mixture is filtered and dried to obtain a magnesium oxide-doped modified filler.

[0059] The mass fraction of the sodium silicate solution in this embodiment is 3-5%; the mass fraction of the lanthanum nitrate solution is 4-6%.

[0060] In S12 of the present embodiment, the stirring speed of the stirring treatment is 550-750 r / min, and the stirring time is 35-45 min; in S13, the ultrasonic power of the ultrasonic immersion is 350-400 W, and the ultrasonic time is 20-30 min.

[0061] Embodiment 1: A method for preparing a bamboo charcoal pot ceramic material, comprising the following steps:

[0062] Step 1: weigh the raw materials according to weight: 25 parts of bamboo charcoal powder, 20 parts of quartz powder, 10 parts of silicon carbide, 10 parts of whisker-based polyphonic balance agent, 8 parts of albite, 7 parts of magnesium oxide-doped filler, and 5 parts of clay;

[0063] Step 2: wet-milling the raw material in step 1 at a ball milling speed of 1000 r / min for 2 h to obtain a ball milled material;

[0064] Step 3: hot-press the ball mill material into a mold, with a hot-pressing pressure of 10 MPa, a pressure time of 1 hour, and a hot-pressing temperature of 60°C. After the hot-pressing is completed, a ball mill body is obtained;

[0065] Step 4: The ball mill is fired and formed, and after the firing is completed, the bamboo charcoal pot ceramic material is obtained.

[0066] The sintering process of this embodiment first adopts sintering at 550° C. for 1 hour, then raises the temperature to 1100° C. at a rate of 2° C. / min and sintering for 2 hours.

[0067] The preparation method of the whisker-based balancing agent of this embodiment is as follows:

[0068] S01: stirring and mixing the aluminum borate whiskers in a sufficient amount of a 5% by mass hydrochloric acid solution, and then washing, filtering and drying to obtain dry aluminum borate whiskers;

[0069] S02: Add 3 parts of nano titanium dioxide and 1 part of cerium oxide to 4 parts of sodium lignin sulfonate solution by weight, and then add 1 part of stearic acid, mix well, and obtain a modified solution;

[0070] The dried aluminum borate whiskers and the modified liquid are stirred and modified in a weight ratio of 2:5, and after the stirring is completed, the mixture is filtered and dried to obtain the modified aluminum borate whiskers;

[0071] S03: The modified aluminum borate whiskers and the balancing liquid are mixed and ball-milled in a weight ratio of 5:3. After the ball-milling is completed, the mixture is washed with water, filtered and dried to obtain a whisker-based polyvalent balancing agent.

[0072] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 2-5%; the stirring speed of the stirring modification treatment is 55 r / min, and the stirring time is 20 min.

[0073] The mixing ball milling process in this embodiment has a ball milling speed of 1000 r / min and a ball milling time of 2 h.

[0074] The Lianheng liquid of this embodiment includes the following raw materials in parts by weight:

[0075] 4 parts of nano-montmorillonite, 3 parts of dopamine hydrochloride solution, 1 part of chitosan solution, 2 parts of silicon carbide and 1 part of lanthanum oxide.

[0076] The mass fraction of the dopamine hydrochloride solution in this embodiment is 2%; the mass fraction of the chitosan solution is 3%.

[0077] The preparation method of the magnesium oxide-doped filler modified in this embodiment is as follows:

[0078] S11: stirring the sepiolite fiber in a sufficient amount of a 5% by mass potassium permanganate solution, then washing, filtering, and drying to obtain dry sepiolite fiber;

[0079] By weight, 4 parts of dry sepiolite fiber, 1 part of silane coupling agent KH550, 2 parts of sodium silicate solution and 1 part of heavy calcium carbonate were mixed and stirred thoroughly to obtain a fiber liquid;

[0080] S12: preheating aluminum nitride at 60° C. for 15 minutes, stirring the preheated aluminum nitride and fiber liquid in a weight ratio of 3:5, and completing the stirring to obtain a fiber-adjusted aluminum nitride agent;

[0081] S13: heat treating the nano-magnesium oxide at 260°C for 10 min, then cooling to 55°C at a rate of 1°C / min, and keeping the temperature;

[0082] The nano-magnesium oxide is immersed in a sufficient amount of lanthanum nitrate solution and fully ultrasonicated, and then filtered and dried to obtain lanthanum-doped nano-magnesium oxide;

[0083] S14: The lanthanum-doped nano-magnesium oxide and the aluminum nitride agent blended with the fiber are mixed and ball-milled in a weight ratio of 5:3 at a ball-milling speed of 1500 r / min for 1 h. After the ball-milling is completed, the mixture is filtered and dried to obtain a magnesium oxide-doped modified filler.

[0084] The mass fraction of the sodium silicate solution in this embodiment is 3%; the mass fraction of the lanthanum nitrate solution is 4%.

[0085] In S12 of the present embodiment, the stirring speed of the stirring treatment is 550 r / min, and the stirring time is 35 min; in S13, the ultrasonic power of the ultrasonic immersion is 350 W, and the ultrasonic time is 20 min.

[0086] Embodiment 2: A method for preparing a bamboo charcoal pot ceramic material, comprising the following steps:

[0087] Step 1: weigh the raw materials according to weight: 30 parts of bamboo charcoal powder, 25 parts of quartz powder, 15 parts of silicon carbide, 14 parts of whisker-based counterbalance agent, 12 parts of albite, 11 parts of magnesium oxide-doped filler, and 10 parts of clay;

[0088] Step 2: wet-milling the raw material in step 1 at a speed of 1500 r / min for 2 h to obtain a ball-milled material;

[0089] Step 3: hot-press the ball mill material into a mold, with a hot-pressing pressure of 15 MPa, a pressure time of 2 h, and a hot-pressing temperature of 65 ° C. After the hot-pressing is completed, a ball mill body is obtained;

[0090] Step 4: The ball mill is fired and formed, and after the firing is completed, the bamboo charcoal pot ceramic material is obtained.

[0091] The sintering process of this embodiment first adopts a sintering temperature of 570° C. for 1 hour, and then increases the temperature to 1150° C. at a rate of 2° C. / min and sintering for 2 hours.

[0092] The preparation method of the whisker-based balancing agent of this embodiment is as follows:

[0093] S01: stirring and mixing the aluminum borate whiskers in a sufficient amount of a 5% by mass hydrochloric acid solution, and then washing, filtering and drying to obtain dry aluminum borate whiskers;

[0094] S02: Add 5 parts of nano titanium dioxide and 3 parts of cerium oxide to 7 parts of sodium lignin sulfonate solution by weight, and then add 2 parts of stearic acid, mix well, and obtain a modified solution;

[0095] The dried aluminum borate whiskers and the modified liquid are stirred and modified in a weight ratio of 2:5, and after the stirring is completed, the mixture is filtered and dried to obtain the modified aluminum borate whiskers;

[0096] S03: The modified aluminum borate whiskers and the balancing liquid are mixed and ball-milled in a weight ratio of 5:3. After the ball-milling is completed, the mixture is washed with water, filtered and dried to obtain a whisker-based polyvalent balancing agent.

[0097] The mass fraction of the sodium lignin sulfonate solution in this example is 5%; the stirring speed of the stirring modification treatment is 750 r / min, and the stirring time is 30 min.

[0098] The mixing and ball milling process in this embodiment was carried out at a ball milling speed of 1200 r / min and the ball milling was carried out for 2 h.

[0099] The Lianheng liquid of this embodiment includes the following raw materials in parts by weight:

[0100] 6 parts of nano-montmorillonite, 4 parts of dopamine hydrochloride solution, 3 parts of chitosan solution, 3 parts of silicon carbide and 2 parts of lanthanum oxide.

[0101] The mass fraction of the dopamine hydrochloride solution in this embodiment is 5%; the mass fraction of the chitosan solution is 6%.

[0102] The preparation method of the magnesium oxide-doped filler modified in this embodiment is as follows:

[0103] S11: stirring the sepiolite fiber in a sufficient amount of a 5% by mass potassium permanganate solution, then washing, filtering, and drying to obtain dry sepiolite fiber;

[0104] By weight, 7 parts of dry sepiolite fiber, 3 parts of silane coupling agent KH550, 6 parts of sodium silicate solution and 3 parts of heavy calcium carbonate were mixed and stirred to obtain a fiber liquid;

[0105] S12: preheating aluminum nitride at 65° C. for 20 minutes, stirring the preheated aluminum nitride and fiber liquid in a weight ratio of 3:7, and completing the stirring to obtain a fiber-adjusted aluminum nitride agent;

[0106] S13: heat treating the nano-magnesium oxide at 270°C for 15 min, then cooling to 55°C at a rate of 3°C / min, and keeping the temperature;

[0107] The nano-magnesium oxide is immersed in a sufficient amount of lanthanum nitrate solution and fully ultrasonicated, and then filtered and dried to obtain lanthanum-doped nano-magnesium oxide;

[0108] S14: The lanthanum-doped nano-magnesium oxide and the aluminum nitride agent blended with the fiber are mixed and ball-milled in a weight ratio of 5:3 at a ball-milling speed of 1500 r / min for 1 h. After the ball-milling is completed, the mixture is filtered and dried to obtain a magnesium oxide-doped modified filler.

[0109] The mass fraction of the sodium silicate solution in this embodiment is 5%; the mass fraction of the lanthanum nitrate solution is 6%.

[0110] In S12 of the present embodiment, the stirring speed of the stirring treatment is 750 r / min, and the stirring time is 45 min; in S13, the ultrasonic power of the ultrasonic immersion is 400 W, and the ultrasonic time is 30 min.

[0111] Embodiment 3: A method for preparing a bamboo charcoal pot ceramic material, comprising the following steps:

[0112] Step 1: weigh the raw materials according to weight: 27.5 parts of bamboo charcoal powder, 22.5 parts of quartz powder, 12.5 parts of silicon carbide, 12 parts of whisker-based polyphonic balancing agent, 10 parts of albite, 9 parts of magnesium oxide-doped modified filler, and 7.5 parts of clay;

[0113] Step 2: wet-milling the raw material in step 1 at a ball milling speed of 1250 r / min for 2 h to obtain a ball milled material;

[0114] Step 3: hot-press the ball mill material into a mold, with a hot-pressing pressure of 12.5 MPa, a pressure time of 1.5 h, and a hot-pressing temperature of 62 ° C. After the hot-pressing is completed, a ball mill body is obtained;

[0115] Step 4: The ball mill is fired and formed, and after the firing is completed, the bamboo charcoal pot ceramic material is obtained.

[0116] The sintering process of this embodiment first adopts sintering at 560° C. for 1 hour, then raises the temperature to 1125° C. at a rate of 2° C. / min and sintering for 2 hours.

[0117] The preparation method of the whisker-based balancing agent of this embodiment is as follows:

[0118] S01: stirring and mixing the aluminum borate whiskers in a sufficient amount of a 5% by mass hydrochloric acid solution, and then washing, filtering and drying to obtain dry aluminum borate whiskers;

[0119] S02: Add 4 parts of nano titanium dioxide and 2 parts of cerium oxide to 5.5 parts of sodium lignin sulfonate solution by weight, and then add 1.5 parts of stearic acid, mix well, and obtain a modified solution;

[0120] The dried aluminum borate whiskers and the modified liquid are stirred and modified in a weight ratio of 2:5, and after the stirring is completed, the mixture is filtered and dried to obtain the modified aluminum borate whiskers;

[0121] S03: The modified aluminum borate whiskers and the balancing liquid are mixed and ball-milled in a weight ratio of 5:3. After the ball-milling is completed, the mixture is washed with water, filtered and dried to obtain a whisker-based polyvalent balancing agent.

[0122] The mass fraction of the sodium lignin sulfonate solution in this example is 3.5%; the stirring speed of the stirring modification treatment is 600 r / min, and the stirring time is 25 min.

[0123] The mixing ball milling process in this embodiment has a ball milling speed of 1100 r / min and a ball milling time of 2 h.

[0124] The Lianheng liquid of this embodiment includes the following raw materials in parts by weight:

[0125] 5 parts of nano-montmorillonite, 3.5 parts of dopamine hydrochloride solution, 2 parts of chitosan solution, 2.5 parts of silicon carbide and 1.5 parts of lanthanum oxide.

[0126] The mass fraction of the dopamine hydrochloride solution in this embodiment is 3.5%; the mass fraction of the chitosan solution is 4.5%.

[0127] The preparation method of the magnesium oxide-doped filler modified in this embodiment is as follows:

[0128] S11: stirring the sepiolite fiber in a sufficient amount of a 5% by mass potassium permanganate solution, then washing, filtering, and drying to obtain dry sepiolite fiber;

[0129] By weight, 5.5 parts of dry sepiolite fiber, 2 parts of silane coupling agent KH550, 4 parts of sodium silicate solution and 2 parts of heavy calcium carbonate were mixed and stirred to obtain a fiber solution;

[0130] S12: preheating aluminum nitride at 62.5° C. for 17 minutes, stirring the preheated aluminum nitride and fiber liquid in a weight ratio of 3:6, and completing the stirring to obtain a fiber-adjusted aluminum nitride agent;

[0131] S13: heat treating the nano-magnesium oxide at 265°C for 12.5 min, then cooling to 55°C at a rate of 2°C / min, and keeping the temperature;

[0132] The nano-magnesium oxide is immersed in a sufficient amount of lanthanum nitrate solution and fully ultrasonicated, and then filtered and dried to obtain lanthanum-doped nano-magnesium oxide;

[0133] S14: The lanthanum-doped nano-magnesium oxide and the aluminum nitride agent blended with the fiber are mixed and ball-milled in a weight ratio of 5:3 at a ball-milling speed of 1500 r / min for 1 h. After the ball-milling is completed, the mixture is filtered and dried to obtain a magnesium oxide-doped modified filler.

[0134] The mass fraction of the sodium silicate solution in this embodiment is 4%; the mass fraction of the lanthanum nitrate solution is 5%.

[0135] In S12 of the present embodiment, the stirring speed of the stirring treatment is 600 r / min, and the stirring time is 40 min; in S13, the ultrasonic power of the ultrasonic immersion is 375 W, and the ultrasonic time is 25 min.

[0136] Comparative Example 1:

[0137] The difference from Example 3 is that no whisker-based counterbalancing agent is added.

[0138] Comparative Example 2:

[0139] The difference from Example 3 is that no modified aluminum borate whiskers are added in the preparation of the whisker-based counterbalancing agent, that is, steps S01 and S02 are cancelled and the modified aluminum borate whiskers in step S03 are removed, and the counterbalancing liquid is directly ball-milled. After the ball milling is completed, the counterbalancing agent is washed, filtered and dried to obtain the whisker-based counterbalancing agent.

[0140] Comparative Example 3:

[0141] The difference from Example 3 is that the modified aluminum borate whiskers are not treated with a modifying liquid.

[0142] Comparative Example 4:

[0143] The difference from Example 3 is that no nano titanium dioxide or cerium oxide is added to the modified solution.

[0144] Comparative Example 5:

[0145] The difference from Example 3 is that no dried aluminum borate whiskers are added to the modified aluminum borate whiskers, that is, step S01 is cancelled and the dried aluminum borate whiskers in step S02 are removed, and the modified liquid is directly stirred. After the stirring is completed, the solution is filtered and dried to obtain the modified aluminum borate whiskers.

[0146] Comparative Example 6:

[0147] The difference from Example 3 is that no balancing liquid is added in the preparation of the balancing agent based on whisker polyadjustment.

[0148] Comparative Example 7:

[0149] The difference from Example 3 is that no filler modified by doped magnesium oxide is added.

[0150] Comparative Example 8:

[0151] The difference from Example 3 is that the lanthanum-doped nano-magnesium oxide is not added in the preparation of the magnesium oxide-modified filler.

[0152] Comparative Example 9:

[0153] The difference from Example 3 is that the lanthanum-doped nano-magnesium oxide is replaced by nano-magnesium oxide.

[0154] Comparative Example 10:

[0155] The difference from Example 3 is that no fiber-blended aluminum nitride agent is added in the preparation of the magnesium oxide-doped modified filler.

[0156] Comparative Example 11:

[0157] The difference from Example 3 is that no preheated aluminum nitride is added in the preparation of the aluminum nitride agent for fiber blending.

[0158] Comparative Example 12:

[0159] The difference from Example 3 is that no fiber liquid is added in the preparation of the aluminum nitride agent for fiber blending.

[0160] Comparative Example 13:

[0161] The difference from Example 3 is that no dry sepiolite fibers are added to the fiber liquid.

[0162] Comparative Example 14:

[0163] The difference from Example 3 is that heavy calcium carbonate and silane coupling agent KH550 are not added to the fiber liquid.

[0164] The conventional performance tests of the products prepared in Examples 1 to 3 and Comparative Examples 1 to 14 were conducted on impact resistance, thermal conductivity and wear resistance. The products were placed at -5°C for 48 hours, then at 70°C for 48 hours, and then scrubbed 10 times with a load of 5N to test the cold and heat resistance and scrubbing stability of the products. The test results are shown in Table 1.

[0165] Table 1 Product performance test results of Examples 1 to 3 and Comparative Examples 1 to 14:

[0166]

[0167] From Examples 1 to 3 and Comparative Examples 1 to 14, it can be concluded that the product of Example 3 has excellent impact resistance, thermal conductivity and wear resistance, and at the same time, the product performance coordination effect is significant, and the product has excellent cold and heat resistance and scrubbing stability effects;

[0168] The present invention does not add a whisker-based counterbalancing agent or a filler modified by doping magnesium oxide, and the performance effect of the product is significantly deteriorated. The two are used in coordination to achieve synergy, and the product performance effect is obvious.

[0169] In the preparation of the whisker-based counterbalancing agent, no modified aluminum borate whiskers were added, the modified aluminum borate whiskers were not treated with a modifying liquid, nano titanium dioxide and cerium oxide were not added to the modifying liquid, and no dried aluminum borate whiskers were added to the modified aluminum borate whiskers. In the preparation of the whisker-based counterbalancing agent, no balancing liquid was added. The performance of the product also showed a trend of deterioration to varying degrees. In particular, the whisker-based counterbalancing agent obtained by the specific method of the present invention without the addition of modified aluminum borate whiskers and balancing liquid had the most obvious product performance effect.

[0170] In the preparation of the magnesium oxide-modified filler, the performance of the product deteriorated significantly when no lanthanum-doped nano-magnesium oxide or fiber-blended aluminum nitride agent was added.

[0171] The lanthanum-doped nano-magnesium oxide is replaced by nano-magnesium oxide, no preheated aluminum nitride is added in the preparation of the fiber-adjusted aluminum nitride agent, no fiber liquid is added in the preparation of the fiber-adjusted aluminum nitride agent, no dry sepiolite fiber is added to the fiber liquid, and no heavy calcium carbonate and silane coupling agent KH550 are added to the fiber liquid. The performance of the product has a tendency to deteriorate to varying degrees. The fiber liquid obtained by the specific method of the present invention is combined with the fiber-adjusted aluminum nitride agent obtained by preheating aluminum nitride and the specific lanthanum-doped nano-magnesium oxide. The product has the most significant performance effect. Other methods are not as obvious as the effect of the present invention.

[0172] Based on the above performance tests, the inventors of the present invention found that Lianheng Liquid has a greater impact on the performance of the product. Based on this, the present invention further studies it.

[0173] Experimental Example 1:

[0174] The only difference from Example 3 is that no nano-montmorillonite is added to the balance solution.

[0175] Experimental Example 2:

[0176] The only difference from Example 3 is that no chitosan solution is added to the balance solution.

[0177] Experimental Example 3:

[0178] The only difference from Example 3 is that no dopamine hydrochloride solution is added to the balance solution.

[0179] Experimental Example 4:

[0180] The only difference from Example 3 is that silicon carbide is not added to the balance solution.

[0181] Experimental Example 5:

[0182] The only difference from Example 3 is that no lanthanum oxide is added to the balance solution.

[0183] The conventional performance tests of the products prepared in Experimental Examples 1 to 5 were conducted on impact resistance, thermal conductivity and wear resistance. The products were placed at -5°C for 48 hours, then at 70°C for 48 hours, and then scrubbed 10 times with a load of 5N to test the cold and heat resistance and scrubbing stability of the products. The test results are shown in Table 2.

[0184] Table 2 Product performance test results of Experimental Examples 1 to 5:

[0185]

[0186] It can be seen from Experimental Examples 1-5 that when nano-montmorillonite is not added to the Lianheng liquid, the performance of the product deteriorates significantly. Secondly, when silicon carbide is not added to the Lianheng liquid, the performance of the product also shows a significant deterioration trend. When lanthanum oxide, chitosan solution and dopamine hydrochloride solution are not added to the Lianheng liquid, the performance of the product all shows a deterioration trend. Only when the Lianheng liquid with the formula of the present invention is used, the performance effect of the product is the most significant. When other methods are used instead, the effects are not as significant as those of the present invention. The Lianheng liquid of the present invention is proprietary.

[0187] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0188] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing a bamboo charcoal pot ceramic material, characterized in that: The following steps are involved: Step 1: weigh the raw materials according to weight: 25-30 parts of bamboo charcoal powder, 20-25 parts of quartz powder, 10-15 parts of silicon carbide, 10-14 parts of whisker-based counterbalancer, 8-12 parts of albite, 7-11 parts of magnesium oxide-doped filler, and 5-10 parts of clay; The preparation method of the whisker-based counterbalancing agent is as follows: S01: stirring and mixing the aluminum borate whiskers in a sufficient amount of a 5% by mass hydrochloric acid solution, and then washing, filtering and drying to obtain dry aluminum borate whiskers; S02: Add 3 to 5 parts of nano titanium dioxide and 1 to 3 parts of cerium oxide to 4 to 7 parts of sodium lignin sulfonate solution by weight, and then add 1 to 2 parts of stearic acid, mix well, and obtain a modified solution; The dried aluminum borate whiskers and the modified liquid are stirred and modified in a weight ratio of 2:5, and after the stirring is completed, the mixture is filtered and dried to obtain the modified aluminum borate whiskers; S03: mixing the modified aluminum borate whiskers and the balancing liquid in a weight ratio of 5:3 and subjecting them to ball milling. After the ball milling is completed, washing, filtering and drying are performed to obtain a whisker-based polyvalent balancing agent. The balance solution comprises the following raw materials in parts by weight: 4 to 6 parts of nano-montmorillonite, 3 to 4 parts of dopamine hydrochloride solution, 1 to 3 parts of chitosan solution, 2 to 3 parts of silicon carbide and 1 to 2 parts of lanthanum oxide; The preparation method of the magnesium oxide-doped filler is as follows: S11: stirring the sepiolite fiber in a sufficient amount of a 5% by mass potassium permanganate solution, then washing, filtering, and drying to obtain dry sepiolite fiber; By weight, 4-7 parts of dry sepiolite fiber, 1-3 parts of silane coupling agent KH550, 2-6 parts of sodium silicate solution and 1-3 parts of heavy calcium carbonate are mixed and stirred to obtain a fiber liquid; S12: preheating aluminum nitride at 60-65° C. for 15-20 minutes to obtain preheated aluminum nitride; stirring the preheated aluminum nitride and fiber liquid in a weight ratio of 3:(5-7), and completing the stirring to obtain a fiber-adjusted aluminum nitride agent; S13: heat treating the nano magnesium oxide at 260-270° C. for 10-15 min, then cooling to 55° C. at a rate of 1-3° C. / min, and keeping the temperature to obtain the heat-insulated nano magnesium oxide; The nano magnesium oxide is immersed in a sufficient amount of lanthanum nitrate solution and fully ultrasonicated, and then filtered and dried to obtain lanthanum-doped nano magnesium oxide; S14: mixing the lanthanum-doped nano-magnesium oxide and the aluminum nitride agent blended with the fiber in a weight ratio of 5:3, and ball milling the mixture at a speed of 1500 r / min for 1 h. After the ball milling is completed, the mixture is filtered and dried to obtain a magnesium oxide-doped modified filler; Step 2: wet-milling the raw material in step 1 at a ball milling speed of 1000-1500 r / min for 2 h to obtain a ball milled material; Step 3: hot-pressing the ball mill material into a mold, with a hot-pressing pressure of 10-15 MPa, a hot-pressing time of 1-2 hours, and a hot-pressing temperature of 60-65°C. After the hot-pressing is completed, a ball mill body is obtained; Step 4: The ball mill is fired and formed, and after the firing is completed, the bamboo charcoal pot ceramic material is obtained.

2. The method for preparing a bamboo charcoal pot ceramic material according to claim 1, characterized in that: The sintering and molding process first adopts a temperature of 550-570° C. for 1 hour, then increases the temperature to 1100-1150° C. at a rate of 2° C. / min, and sinters for 2 hours.

3. The method for preparing a bamboo charcoal pot ceramic material according to claim 1, characterized in that: The mass fraction of the sodium lignin sulfonate solution is 2-5%.

4. The method for preparing a bamboo charcoal pot ceramic material according to claim 1, characterized in that: The stirring speed of the stirring modification treatment is 550-750 r / min, and the stirring time is 20-30 min.

5. The method for preparing a ceramic material for a bamboo charcoal pot according to claim 1, characterized in that: The mixing and ball milling treatment in S03 is carried out at a speed of 1000-1200 r / min for 2 h.

6. The method for preparing a ceramic material for a bamboo charcoal pot according to claim 1, characterized in that: The mass fraction of the dopamine hydrochloride solution is 2-5%.

7. The method for preparing a ceramic material for a bamboo charcoal pot according to claim 1, characterized in that: The mass fraction of the chitosan solution is 3-6%.

8. The method for preparing a ceramic material for a bamboo charcoal pot according to claim 1, characterized in that: The mass fraction of the sodium silicate solution is 3-5%.

9. The method for preparing a ceramic material for a bamboo charcoal pot according to claim 1, characterized in that: The mass fraction of the lanthanum nitrate solution is 4-6%.

10. The method for preparing a ceramic material for a bamboo charcoal pot according to claim 1, characterized in that: The stirring speed of the stirring treatment in S12 is 550~750r / min, and the stirring time is 35~45min; the ultrasonic power of the ultrasonic immersion in S13 is 350~400W, and the ultrasonic time is 20~30min.

Citation Information

Patent Citations

  • High-strength and high-toughness graphene composite ceramics

    CN108546105A

  • Antiskid glaze, glazed ceramic product and preparation method thereof

    CN119059736A